ESTIMASI NILAI RIPITABILITAS DAN NILAI MPPA (MOST PROBABLE PRODUCING ABILITY) BOBOT SAPIH SAPI PERANAKAN ONGOLE (PO) DI DESA WAWASAN KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Ficke Rahmawati, M. Dima Iqbal Hamdani, Ali Husni dan Sulastri (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This research aims to estimate the value of ripeatability and Most Probable Producing Ability (MPPA) for weaning weight of Ongole grade cattle. This research wascarried out on 29 June--29 July 2018 in Wawasan Village, Tanjungsari District, South Lampung Regency, Lampung Province. The research material used consisted of the age of the mother at the time of delivery, calf birth weight, calf weaning age, calf weaning weight, and recording data in 2013--2017 . This study used a survey method. Data analysis was carried out by estimating corrected weaning weights, ripitability values, and MPPA. Based on the results of this study the average value of corrected weaning weight was 111,81±13,56; ripitability value was 0,6, and the average value of MPPA was 245,98±29,83. Ripitability value of 0.6 estimated in this study included in the high category. This study also showed that there were 56,76% of cows which had MPPA values above the average (245,98±29,83). Keywords: MPPA, PO cattle, Ripitability estimate, Weaning weight.